1977
DOI: 10.1044/jshd.4201.60
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Auditec of St. Louis Cassette Recordings of NU-6 and CID W-22 on a Normal-Hearing Population

Abstract: Articulation functions were generated on a normal-hearing population with the Auditec of St. Louis cassette recordings of the NU-6 and CID W-22 speech discrimination tests. Both tests were similar and yielded slopes of about 4.4%/dB. Each gave a speech discrimination score of approximately 95% at 32 dB SL. Speech reception thresholds were obtained with monitored live voice and yielded good test-retest consistency. Speech thresholds were about 9 dB better than the ANSI (1969) specifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…They are also comparable to discrimination scores of normal adults on NU-6 lists (Larson, Petersen and Jacquot, 1974;Beattie, Edgerton and Svihovec, 1977) . No significant response differences were observed between experimental and control groups exposed to time altered speech.…”
Section: Resultssupporting
confidence: 71%
“…They are also comparable to discrimination scores of normal adults on NU-6 lists (Larson, Petersen and Jacquot, 1974;Beattie, Edgerton and Svihovec, 1977) . No significant response differences were observed between experimental and control groups exposed to time altered speech.…”
Section: Resultssupporting
confidence: 71%
“…Beattie et al (1977) reported a mean slope of 4.2 %/dB for the NU-6 word lists and a mean slope of 4.6 %/dB for the CID W-22 word lists. A more recent study found that the recordings from the Auditec of St. Louis CD, NU-6 and CID W-22 word lists had means of 4.4 %/dB and 4.8 %/dB, respectively (Wilson & Oyler, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Han et al [16] 4.1 English NU-6, Beattie et al [36] 4.2 English CIDW-22, Beattie et al [36] 4.6 English NU-6, Wilson and Oyler [37] 4.4…”
Section: Mandarinmentioning
confidence: 99%